Body-temperature programmable soft-shape memory hybrid sponges for comfort fitting - Naveen, Balasundaram Selvan (2021)
Porous shape memory hybrids are fabricated with different matrix (silicone) hardness and different inclusion (polycaprolactone, PCL) ratios. They are characterized to obtain their mechanical response to cyclic loads (with/without pre-straining/programming) and their shape memory performances after body-temperature programming are investigated. These materials are lightweight due to their porous structures. Wetted hydrogels used in the fabrication process for creating pores are reusable and hence this process is eco-friendly. These porous shape memory hybrids exhibit the good shape memory effect of around 90% with higher inclusion (PCL) ratios, which is better than the solid versions reported in the literature. Hence, it is concluded that these materials have great potential to be used in, for instance, insoles and soles for comfort fitting, as demonstrated.